Crystal structure of a carborane endo/exo-dianion and its use in the synthesis of ditopic ligands for supramolecular frameworks. Issue 14 (4th January 2018) - Zhang, Kang; Shen, Yunjun; Liu, Jiyong; Spingler, Bernhard; Duttwyler, Simon
Abstract : The crystal structure of a monocarba- closo -dodecaborate endo / exo -dianion is reported, featuring a delocalized endohedral charge and a sigma-type C–[Li] moiety. Abstract : The crystal structure of the deprotonated monocarba- closo -dodecaborate [12-CN-CB11 H11 ] − is reported. This dianion, featuring a delocalized endohedral negative charge and an exo -cluster C–[Li] moiety, was used for the synthesis of ditopic ligands with the potential to form novel supramolecular frameworks.